Box drill training as an effective method to improve agility in futsal players - Dessy Ramadhanti; Syamsuramel Syamsuramel; Ahmad Richard Victorian (Universitas Sriwijaya, 2025)
Research Problems: This research aims to determine the effect of box drill exercises on agility ability in futsal extracurricular activities at state primary school 58 Lubuk Linggau. Research Objectives: This research aims to determine the effect of box drill exercises on agility ability in futsal extracurricular activities at state primary school 58 Lubuk Linggau. Methods: The method used in this research is quasi-experiment. Using a research design, namely a one-group pretest-posttest design. The research sample was thirty students at state primary school 58 Lubuk Linggau. The research location was conducted at state primary school 58 Lubuk Linggau. Results: Data from the pretest results obtained from 20 students obtained the poor category, and the students who received the very few categories were 10 students. Data from the posttest results were obtained from 30 students in the good category. The value obtained by the Independent Sample Test count was 1.474. The research results have an effect if 1.474 0.05 then Ha is accepted. After conducting the hypothesis testing criteria using the t-test, there is tcount 5.896 and ttable 1.69, then tcount > ttable with a confidence level of 0.95 (α 0.05) with a sample size of (N 30). Conclusion: It was explained that there was a significant difference, which means (Ha) there was an influence of box drill exercises on agility ability in futsal extracurricular activities at state primary school 58 Lubuk Linggau.